Therapeutic Effects of Combination Therapy and Photobiomodulation Therapy on Retinal Regeneration - Ahrabi, Behnaz; Omidvari, Samareh; Mollazadeh Ghomi, Shamim; Ahmady Roozbahany, Navid; Vafaei-Nezhad, Saeed; Shirazi Tehrani, Atefeh; Abbaszadeh, Hojjat-allah; Darabi, Shahram (Journal of Lasers in Medical Sciences, 2022)
Introduction: Macular edema (ME) is produced by central extravascular inflammation of the macula subsequent to a major loss of visual action. Macular edema can happen at any phase of diabetic retinopathy, whether non-proliferative or proliferative retinopathy. Method and material: Articles were collected from four electronic databases PubMed, Google Scholar Web of Science from 2000 to 2022 and electronically to study the effects of macular laser grid photocoagulation on Diabetic macular edema or Cystoid macular edema through the keywords " macular laser photocoagulation ", " macular edema ", " Cystoid macular edema ", " Intravitreal pharmacotherapies ", " Antivascular endothelial growth factor “, were searched about 219 articles found in google scholar and 165 articles in PubMed, that 58 articles were included in the study. Result: In this study, the effects of various laser photocoagulation such as Focal and/or grid macular laser, subthreshold micropulse laser (SMPL), and Intravitreal pharmacotherapies (Corticosteroids such as triamcinolone acetonide, fluocinolone, Bevacizumab, and dexamethasone) on macular edema were investigated. A few studies had shown that the effects of corticosteroids are more effective than lasers, and a number of studies have found the effects of lasers and the combined effects of lasers with corticosteroids to be more effective. Also, some studies have also shown that the frequency and duration of follow-up and concentrations of intravitreal pharmacotherapies are effective in increasing visual outcomes. Conclusion: The results of studies showed that although corticosteroids have side effects, the combined effects of corticosteroids with subthreshold micropulse laser are effective in increasing visual acuity (VA) and central macular thickness (CMT).